Prefrontal cortex modulates posterior alpha oscillations during top-down guided visual perception - Helfrich, Randolph F. (Proc Natl Acad Sci U S A, 2017)
Conscious visual perception is proposed to arise from the selective synchronization of functionally specialized but widely distributed cortical areas. It has been suggested that different frequency bands index distinct canonical computations. Here, we probed visual perception on a fine-grained temporal scale to study the oscillatory dynamics supporting prefrontal-dependent sensory processing. We tested whether a predictive context that was embedded in a rapid visual stream modulated the perception of a subsequent near-threshold target. The rapid stream was presented either rhythmically at 10 Hz, to entrain parietooccipital alpha oscillations, or arrhythmically. We identified a 2- to 4-Hz delta signature that modulated posterior alpha activity and behavior during predictive trials. Importantly, delta-mediated top-down control diminished the behavioral effects of bottom-up alpha entrainment. Simultaneous source-reconstructed EEG and cross-frequency directionality analyses revealed that this delta activity originated from prefrontal areas and modulated posterior alpha power. Taken together, this study presents converging behavioral and electrophysiological evidence for frontal delta-mediated top-down control of posterior alpha activity, selectively facilitating visual perception.